The genesis, development and impact of the African Teacher's Association of South Africa, 1921-1980 : an historical educational survey - Mphahlele, Dixon Makgeledisa (My University, 1981)
Refer to the document
Thesis (M. Ed.) -- University of Limpopo, 1981
Keywords: African teachers; Black education; Teacher's unions; Teachers' unions; Blacks -- Education -- South Africa; Education -- Societies, etc.